Mendhak: Studi tentang Simbol dalam Ritual Tahunan di Desa Tlemang, Kabupaten Lamongan, Jawa Timur - , BIMO HARYO YUDHANTO, Agus Indiyanto, S.Sos., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discuss about a mendhak ritual which is believed as an honour to the ancestor of Tlemang village. Today, Tlemangâs people still conduct the ritual regularly with their common awareness. Based on the ritual implementation, it cannot be separated from the context of Tlemangâs societies. Tlemangâs people is an agriculture societies who live in the area that is not ideal for farming. In that condition, the mendhak ritual is still conducted. The ritual processes have to be held every year in 24-27 Jumadilawwal. It consists of three activities such as cleaning the springs (bersih sendhang), cleaning the grave, (bersih makam), Krucilâs puppet show and cooking sanggring soup. There is no toleration to change the manner and time in conducting this ritual. Humanâs life is loaded with a variety of symbols. Therefore, all of the things cannot be understood explicitly. To findout whether the mendhak ritual represents Tlemangâs society, every meaning in the ritual processes should be revealed. Disclosure of these meanings is not only to identify base ideological ritual, but also open analysis knowledge upon ordinances and historical basis which is one of the reason in mendhak ritual . Symbol Identification looked done with review photographs during the implementation of mendhak ritual. Photographs will be helpful for the identification processes to reach the final result in this study. A symbol in ritual has relations with the socio-culture environment public executioner. Explicitly, mendhak ritual conducted by tlemangâs people shows that they are agricultural societies. It implied in significance contained in every rite in the series of mendhak ritual. As the activity which has solid meaning in every part ritual, there are idea system as the basis ideological, who then came into the shop social and objects culture. Each rites has a message that interconnected. Based on all of the rites, mendhak ritual proved that it can attend the life dynamics of agricultural socities in every riteâs part Key words : ritual, symbol, mendhak